Sovyet Basınında 12 Eylül 1980 Darbesi: Pravda ve İzvestiya Gazeteleri - Temi̇r, Erkam (Ataturk Universitesi, 2021)
Although it has been 40 years since the September 12, 1980 military coup in Turkey, its effects on administration, politics and society are still evident. But the foreign policy background regarding the coup could not go beyond a public perception that the coup was supported by the USA. There is no public perception about the attitude of the USSR regarding the coup, which expected to be a party to the conflicts in Turkey at that time and which is anti-US in bipolar world. In this study, the stance of the USSR on the September 12, 1980 coup was examined through the news in the Soviet press. The aim is to reveal view of the Soviet newspapers (therefore the USSR’s) about September 12 coup. The four-month publication period of Pravda and Izvestiya newspapers between September 11, 1980 and January 13, 1981 was determined as a sample. In this period, a total of 47 news related to the subject were determined and this news were evaluated with a hermeneutic approach.

12 Eylül 1980 darbesinin üzerinden 40 yıl geçmesine rağmen darbenin yönetim, siyaset ve toplum üzerindeki etkileri hala kendini göstermektedir. Darbeye ilişkin dış politik arka plan ise darbenin ABD tarafından desteklendiği yönündeki bir kamuoyu algısının ötesine gidememiştir. Dönemin Türkiye’sinde yaşanan çatışmaların tarafı olması beklenen ve iki kutuplu dünyada ABD’nin karşıtı olan SSCB’nin darbeye ilişkin tutumu konusunda bir kamuoyu algısı oluşmamıştır. Bu çalışmada, 12 Eylül 1980 darbesine ilişkin SSCB’nin tutumu Sovyet basınında yer alan haberler üzerinden irdelenmiştir. Amaç Sovyet gazetelerinin ve dolayısıyla SSCB’nin 12 Eylül darbesine nasıl baktığını ortaya koymaktır. Pravda ve İzvestiya gazetelerinin 11 Eylül 1980- 13 Ocak 1981 tarihleri arasındaki dört aylık yayım dönemi örneklem olarak belirlenmiştir. Bu aralıkta konuya ilişkin toplam 47 haber tespit edilmiş ve bu haberler yorumcu bir yaklaşımla değerlendirilmiştir.
Keywords: Darbe; Eylül; Sovyet basını; Pravda; İzvestiya; Coup; September 12; Soviet press; Pravda; Izvestia; 16. Peace & justice